In vivo screening and evaluation of four herbs against MRSA infections - Najma Arshad; Arifa Mehreen; Iram Liaqat; Muhammad Arshad; Humera Afrasiab (BMC, 2017)
Abstract Background Recently, we reported high in vitro antibacterial efficacy of Althaea officinalis, Ziziphus jujuba, Cordia latifolia and Thymus vulgaris out of a total 21 plants against wide range of bacteria including MRSA. This study was therefore, designed to confirm efficacy of these four herbs against MRSA in an animal model. Methods A pilot study was conducted to establish the dose of S. aureus (KY698020) required to induce clinical infection. Afterword, in main trial, efficacy of aforementioned plant extracts on the course of sore throat was checked by evaluating general health, gross lesion score, bacterial load and hematology in mice. Results Pilot study revealed that 40 μl dose of 107 CFU/ml could induce infection which persist upto 08 days post infection. Mice treated with T. vulgaris and Z. jujuba showed reduction in gross lesion score of both heart and lungs. Treatment with only some plants could significantly decrease bacterial load of throat (T. vulgaris) heart, blood and joint (C. latifolia, and T. vulagris). Hematological indicators confirmed in vivo control of MRSA infection in all treatment groups except A. officinalis. Conclusion This is first report confirming in vivo anti-MRSA potential of C. latifolia and T. vulgaris and highlight the need to explore bioactive constituents of these plants. Moreover, previously reported in vitro antibacterial efficiency of A. officinalis could not be validated in current study.